2003
DOI: 10.2514/2.2021
|View full text |Cite
|
Sign up to set email alerts
|

Soot Surface Growth in Laminar Hydrocarbon/Air Diffusion Flames

Abstract: The structure and soot surface growth properties of round laminar jet diffusion flames were studied experimentally. Measurements were made along the axes of ethylene-, propylene- traversedthe flames when moving to-and-fromthe flame axeswasestablished in two ways: (1) sampling in the region prior to the onsetof soot formation along the axesof the flames (but where there was a well-developedannularsoot-containingregion nearthe edge of the region exhibiting yellow soot luminosity) properly indicatedthat no soot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 50 publications
7
40
0
Order By: Relevance
“…Cases 1 and 2 reveal the sensitivity of soot yields to the soot surface growth mechanism. Kazakov and co-workers' model [34], recommended by El-Leathy and colleagues' empirical study [35], produces a soot yield almost one order of magnitude higher than that of Appel and co-workers' [26] model. Cases 2 and 3 illustrate the sensitivity of soot yields to the steric factor.…”
Section: Key Sensitivities In Soot Predictionsmentioning
confidence: 94%
See 1 more Smart Citation
“…Cases 1 and 2 reveal the sensitivity of soot yields to the soot surface growth mechanism. Kazakov and co-workers' model [34], recommended by El-Leathy and colleagues' empirical study [35], produces a soot yield almost one order of magnitude higher than that of Appel and co-workers' [26] model. Cases 2 and 3 illustrate the sensitivity of soot yields to the steric factor.…”
Section: Key Sensitivities In Soot Predictionsmentioning
confidence: 94%
“…The correlation in [26] gives steric factor values that are less than 0.4 for any temperature. The correlation was adjusted in Cases 3 and 4 so that the values of α are in the range 0.9-1.0, as suggested by El-Leathy et al [35]. In all four cases, the P 1 -gray Fig.…”
Section: Key Sensitivities In Soot Predictionsmentioning
confidence: 99%
“…Experimental studies have indicated that soot surface reactivity is a function of temperature [3,5,[6][7][8][19][20][21][22][23][24][25][26]. Thus, as the first attempt to define a function for a, a comparison was made between the reference a for each flame to the corresponding peak flame temperature, and to the instantaneous temperature at the location peak soot concentration on the wings.…”
Section: Thermal Agementioning
confidence: 99%
“…While initially a constant fraction of active sites was used with the kinetic soot model [1,3], it was later expressed as a function of flame temperature [20], and subsequently as a function of flame temperature and mean particle size [10]. Several studies measured the ageing parameter, a, based on the HACA surface growth scheme in laminar premixed and diffusion flames with different fuels, pressures, and flame temperatures, and proposed a temperature dependent function for the ageing parameter [23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty of measuring soot properties in turbulent flames due to their fluctuating flow fields have motivated studies of laminar flames, which are experimentally and computationally more tractable. Since 1983, there have been papers published on two popular configurations for experimental studies of soot properties, which are the coflow and counterflow laminar flames (Kent et al 1981;Santoro et al 1983;Santoro et al 1987;Glassman 1989;Dobbins et al 1990Dobbins et al , 1998Sunderland and Faeth 1996;Kennedy et al 1996;Kang et al 1997;Zhang and Megaridis 1998;Mohammed et al 1998;Hepp and Siegmann 1998;Smooke et al 1999;Xu and Faeth 2002;El-Leathy et al 2003;D'Anna et al 2005;McCrain and Roberts 2005). The center of attention in most of these studies has been the measurement of the soot volume fraction, which is needed for estimating particle formation/growth rates.…”
Section: Previous Researchmentioning
confidence: 99%